Seeking attention versus seeking approval: How conspicuous consumption differs between grandiose and vulnerable narcissists. Issue 3 (14th January 2020) - Neave, Lydia; Tzemou, Effy; Fastoso, Fernando
Abstract: Narcissism, a personality trait characterized by entitlement and conceit, is increasingly prevalent in society. Two subtypes of narcissism exist: grandiose narcissism (characterized by arrogance and dominance) and vulnerable narcissism (characterized by social insecurity and overreliance on others' feedback). We posit that both narcissistic subtypes will engage in ostentatious, showy purchases, that is, conspicuous consumption. Since the two subtypes differ so profoundly in their self‐esteem regulation strategies, we further posit that their motivations to consume conspicuously may vary. Specifically, we hypothesize that grandiose narcissists' conspicuous consumption will be driven by their need‐for‐uniqueness, whilst that of vulnerable narcissists by their need to avoid social disapproval. We test our hypotheses using data obtained from 382 participants. Our results support our expectations that both narcissism subtypes predict conspicuous consumption and that the relationship between grandiose narcissism and conspicuous consumption is mediated by their need‐for‐uniqueness. Meanwhile, we find that approval‐seeking (AS) is only a marginally significant mediator of vulnerable narcissism and conspicuous consumption in females. We discuss theoretical and managerial implications.